Conducting Critical Research on Powerful Organisations - Stefan Holgersson; Malin Wieslander (Nordisk Politiforskning)
Abstract Independence and integrity in research are prerequisites for objective and ethically responsible research. At the same time, image promotion plays a significant role in many contemporary organisations, and this might influence how research is carried out and presented. The article suggests that organisational branding is significant to understand the conditions in which researchers conduct and present critical research on powerful organisations. In this article we explore what prevents researchers from challenging the police’s brand and how researchers can act when their results do so. The results are based on several sources of data, such as field notes, public records, media statements, research reports and interviews with researchers who have presented critical research.